In Vivo Analysis Of Pandanus Tectorius Fruit Extract Gel: Modulation Of Epithelialization, Collagen Synthesis, And Fibroblast Proliferation In Wound Healing - Afifah Sekarkusuma; Vanessa Hedyana Putri; Shehnaz Neisa Rasyid; Maritza Cahya Kusuma (Pelopor Publikasi Akademika, 2025)
Herbal therapies are increasingly explored for wound management due to their perceived safety compared with synthetic agents. Pandanus tectorius contains bioactive compounds with potential benefits for tissue repair; however, evidence supporting its efficacy in incision remains limited. This study aimed to evaluate the effects of Pandanus tectorius ethanol extract gel on epithelialization, collagen density, and fibroblast proliferation in incision wounds of Rattus norvegicus. A post-test-only control-group experimental design was conducted using 30 white rats, allocated into five groups: positive control (Bioplacenton®), negative control (gel base), and extract gel treatments at concentrations of 10%, 20%, and 30%. Histological evaluations of epithelialization, fibroblast count, and collagen density were performed. Data were analyzed using ANOVA with Duncan’s post hoc test. Fibroblast proliferation differed significantly among groups (p < 0.001; ?² = 0.590). The 20% and 30% extract groups demonstrated the highest fibroblast counts. Collagen density showed a non-normal distribution in the negative control group, though overall variances were homogeneous. ANOVA did not reveal statistically significant differences in collagen density; however, Duncan’s test suggested a tendency toward increased collagen formation in the 30% extract group. The results indicate that Pandanus tectorius extract gel enhances tissue regeneration by significantly promoting epithelialization and fibroblast proliferation. Although the collagen in improvement was not statistically significant, the observed upward trend supports the extract’s potential role in extracellular matrix formation. Overall, Pandanus tectorius fruit extract gel shows promise as a natural wound-healing agent, warranting further research to optimize doses and assess clinical applicability.